-5²+3:[7-(-4):(-1) =?
larireval:
-25+3:(7+4:(-1))= -25+3:(7-4)= -25+3:3=-24
Răspunsuri la întrebare
Răspuns de
0
Răspuns:
1) (-4) :(-1) =4
2) -7-4=3
3) -5²=25
4) 3:3=1
5) 25+1=26
Răspuns de
0
Răspuns:
-5²+3:[7-(-4):(-1) =
+25+3[7-4:(-1)]=
+25+3(7+4)=
+25+3×11
+25+33=58
Sper ca te-am ajutat!!
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Istorie,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă